2022
DOI: 10.3389/fnins.2022.970925
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effects of glucagon-like peptide 1 in Alzheimer’s and Parkinson’s disease: An in-depth review

Abstract: Currently, there is no disease-modifying treatment available for Alzheimer’s and Parkinson’s disease (AD and PD) and that includes the highly controversial approval of the Aβ-targeting antibody aducanumab for the treatment of AD. Hence, there is still an unmet need for a neuroprotective drug treatment in both AD and PD. Type 2 diabetes is a risk factor for both AD and PD. Glucagon-like peptide 1 (GLP-1) is a peptide hormone and growth factor that has shown neuroprotective effects in preclinical studies, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 580 publications
0
68
0
1
Order By: Relevance
“…It showed that liraglutide treated patients performed significantly better than placebo in temporal lobe and whole cortical magnetic resonance imaging volume and cognitive function [77] [78,79]. An in-depth review on the pathophysiology, animal studies and clinical trials of the neuroprotective mechanisms of GLP-1RAs was recently published [80].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…It showed that liraglutide treated patients performed significantly better than placebo in temporal lobe and whole cortical magnetic resonance imaging volume and cognitive function [77] [78,79]. An in-depth review on the pathophysiology, animal studies and clinical trials of the neuroprotective mechanisms of GLP-1RAs was recently published [80].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The NTS neurons create proglucagon and/ or GLP-1-positive projections that are directed into the olfactory bulb, several hypothalamic nuclei, the bed nucleus of the stria terminalis, the lateral and medial septal nuclei, the amygdaloid complex, the septohippocampal area, the nucleus accumbens, and, less frequently, the medullary reticular formation, dorsal motor nucleus of the vagus, and the cortex. The GLP-1R is broadly distributed in the CNS, in contrast to the NTS, where GLP-1 production and distribution are limited [4].…”
Section: Neuroprotective Properties Of Glucagon-like Peptide-1mentioning
confidence: 99%
“…GLP-1R/gastric inhibitory polypeptide receptor (GIPR) dual agonists inhibited microgliosis, astrogliosis, and the expression of toll-like receptor-4 in a manner comparable to GLP-1 mimetics, however, they had a greater impact. Analogs of the GLP-1R (such as oxyntomodulin and exenatide) promote synaptogenesis, preserve synapses, increase hippocampus synaptic plasticity, and improve learning and memory [4,49].…”
Section: Neuroprotective Properties Of Glucagon-like Peptide-1mentioning
confidence: 99%
See 2 more Smart Citations